2013
DOI: 10.1073/pnas.1315512110
|View full text |Cite
|
Sign up to set email alerts
|

Fibrinogen-specific antibody induces abdominal aortic aneurysm in mice through complement lectin pathway activation

Abstract: Abdominal aortic aneurysm (AAA) is a common vascular disease associated with high mortality rate due to progressive enlargement and eventual rupture. There is currently no established therapy known to alter the rate of aneurysmal expansion. Thus, understanding the processes that initiate and sustain aneurysmal growth is pivotal for the development of medical therapies aimed at halting disease progression. Using an elastase-induced AAA mouse model that recapitulates key features of human AAA, we previously repo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
42
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(46 citation statements)
references
References 47 publications
(74 reference statements)
1
42
0
Order By: Relevance
“…The animal protocol is subjected to The generation and purification of a His-tagged mouse TSR5/6 (mTSR5/6) has been previously described. (27) In brief, recombinant mouse properdin cDNA encoding TSRs 5 and 6 was amplified using PCR methodology and cloned into the pET28a + expression vector (EMD/Millipore, Billerica, MA). The resulting plasmids were transformed into E. coli strain BL21(DE3) RIL codon plus (Agilent Technologies, Santa Clara, CA).…”
Section: Animalsmentioning
confidence: 99%
See 2 more Smart Citations
“…The animal protocol is subjected to The generation and purification of a His-tagged mouse TSR5/6 (mTSR5/6) has been previously described. (27) In brief, recombinant mouse properdin cDNA encoding TSRs 5 and 6 was amplified using PCR methodology and cloned into the pET28a + expression vector (EMD/Millipore, Billerica, MA). The resulting plasmids were transformed into E. coli strain BL21(DE3) RIL codon plus (Agilent Technologies, Santa Clara, CA).…”
Section: Animalsmentioning
confidence: 99%
“…Properdin specificity was confirmed by a Western blot analysis that compared antibody reactivity to normal mouse serum versus serum derived from properdin-deficient mice. (27) Clones H4 and E12 were selected for the studies presented herein. …”
Section: Generation Of Hamster Anti-mouse Properdin Monoclonal Antibomentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, reconstitution with natural IgG to the WT level rendered uMT mice susceptible to AAA formation accompanied by elastic fiber fragmentation and smooth muscle cell (SMC) depletion [19]. Subsequently, they further found that the natural anti-fibrinogen IgG deposited in elastase-perfused aortic tissues induces AAA by activating the complement lectin pathway [32]. After the three complement pathways converge in the formation of C3 convertase, they proceed on a common pathway that mediates inflammation and immunity through macrophage activation and cell death (the membrane attack complex, MAC).…”
Section: The Production Of Immunoglobulinsmentioning
confidence: 99%
“…AAAP-40, which has homologies with elastin-associated microfibrils, has been shown to be similar to three chains of fibrinogen [30,31]. Zhou et al [32] induced mice AAA with a natural IgG that binds to fibrinogen deposited in elastase-perfused aortic tissues. Furthermore, by using 2-dimensional electrophoresis and western blotting, Takashi et al detected CA1 in AAA wall samples were modified to express neoepitope(s) [33].…”
Section: The Role Of B Cells In Aaamentioning
confidence: 99%